Turning point in COVID-19 severity and fatality during the pandemic: a national cohort study in Qatar - Roberto Bertollini; Adeel Ajwad Butt; Peter Coyle; Andrew Jeremijenko; Anvar Hassan Kaleeckal; Riyazuddin Mohammad Shaik; Gheyath K Nasrallah; Hadi M Yassine; Mohamed H Al-Thani; Zaina Al-Kanaani; Mohamed Ghaith Al-Kuwari; Abdullatif Al-Khal; et al. (BMJ Publishing Group, 2023)
Objective To assess the evolution of COVID-19 severity and fatality in a unique setting that consistently applied, throughout the pandemic, rigorous and standardised criteria for defining severe COVID-19 outcomes.Methods and analysis We conducted a national cohort study on 312 109 Qatari citizens to investigate incidence of severe, critical or fatal COVID-19 classified according to the WHO criteria between 28 February 2020 and 21 April 2023. Incidence rates for severe, critical or fatal COVID-19 were estimated during the pre-omicron phase, first omicron wave, combined phases and throughout the pandemic.Results Cumulative incidence of severe, critical or fatal COVID-19 after 3.14 years of follow-up was 0.45% (95% CI 0.43% to 0.47%). Incidence rate for severe, critical or fatal COVID-19 throughout the pandemic was 1.43 (95% CI 1.35 to 1.50) per 1000 person years. In the pre-omicron phase, first omicron wave, and combined phases, it was 2.01 (95% CI 1.90 to 2.13), 3.70 (95% CI 3.25 to 4.22) and 2.18 (95% CI 2.07 to 2.30) per 1000 person years, respectively. The post-first omicron phase saw a drastic drop to 0.10 (95% CI 0.08 to 0.14) per 1000 person years, a 95.4% reduction. Among all severe, critical and fatal cases, 99.5% occurred during the primary infection. Cumulative incidence of fatal COVID-19 was 0.042% (95% CI 0.036% to 0.050%), with an incidence rate of 0.13 (95% CI 0.11 to 0.16) per 1000 person years. In the post-first omicron phase, incidence rate of fatal COVID-19 decreased by 90.0% compared with earlier stages. Both severity and fatality exhibited an exponential increase with age and a linear increase with the number of coexisting conditions.Conclusion The conclusion of the first omicron wave was a turning point in the severity of the pandemic. While vaccination and enhanced case management reduced severity gradually, the rapid accumulation of natural immunity during the first omicron wave appears to have played a critical role in driving this shift in severity.